TODAY’S BULGARIAN BOOK PUBLISHING – SURPLUS AND SHORTAGE - Albert Benbassat (Издател, 2025)
The article examines the excess in the publishing of contemporary Bulgarian authors. Statistical data provided by the National Statistical Institute indicate that the fiction published in our country in recent years is approximately one third of the entire book production. Therefore, our book market is oversaturated with Bulgarian authors, but publishing houses continue to compete to publish them. And with few exceptions, the criterion of quality is increasingly eroding. Publishing demand does not correspond to the supply of good literature. Most of the domestic bestsellers are the result of a false trend that exploits the naivety (to put it mildly!) of that part of the population that does not have lasting reading attitudes and the corresponding intellectual capacity. On the other hand, for more than thirty years there have been no multi-volume editions of the Bulgarian classics. Entire generations have grown up deprived of the opportunity to own and read the complete collections of works by Ivan Vazov, Aleko Konstantinov, Elin Pelin, Yordan Yovkov, Anton Strashimirov, and many more classics. This opens up a huge cultural gap and completely distorts the perceptions of these generations about the appearance and messages of Bulgarian literature from the past. Another problem under consideration is the so-called digital marketing. There are attempts at such marketing in our country, mainly by online bookstores that can afford it purely financially, but it is still lacking among the publishing houses themselves. Their manifestations in some of the directions of digital marketing are incidental, but there is no overall concept that can be applied purposefully and constantly. There is also a lack of sufficiently prepared personnel, because in addition to good knowledge of digital marketing, the book business is a difficult niche to master. Therefore, the digital book marketer needs to be, first of all, a good professional publisher, and then to become professional in this field as well.